2001
DOI: 10.1067/mva.2001.113976
|View full text |Cite
|
Sign up to set email alerts
|

Expression of molecular mediators of apoptosis and their role in the pathogenesis of lower-extremity varicose veins

Abstract: The entry of smooth muscle cells into the apoptotic pathway may be regulated by the induction of bax in this model, because there is significant presence of this pro-apoptotic protein in healthy veins. Both bax and PARP are downregulated in varicose veins, as compared with healthy veins, and this may play a significant role in the pathogenesis of varicose veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 20 publications
3
59
1
3
Order By: Relevance
“…Nevertheless, apoptosis was increased in endothelial cells and cells in the adventitia of varicose veins. Our fi ndings confi rm the limited occurrence of programmed cell death in varicose veins [20,21] .…”
Section: Discussionsupporting
confidence: 52%
“…Nevertheless, apoptosis was increased in endothelial cells and cells in the adventitia of varicose veins. Our fi ndings confi rm the limited occurrence of programmed cell death in varicose veins [20,21] .…”
Section: Discussionsupporting
confidence: 52%
“…Dysregulated apoptosis and cell cycle dysfunction occur in varicose veins 90 -94 . The overall number of apoptotic cells and activity are reduced in varicose compared with non-varicose veins 92,93,95 . Dedifferentiation of SMCs may be due to dysregulated apoptosis 96 .…”
Section: Smooth Muscle Cell Proliferation and Migrationmentioning
confidence: 99%
“…Bax is a member of the bcl-2 family and an inducer of apoptosis. PARP is an enzyme involved in genome surveillance and DNA repair, and is a macromolecular downstream substrate of apoptosis 93 . It has been demonstrated immunohistochemically that the expression of bax and caspase 9 is significantly reduced in SMCs from varicose compared with non-varicose veins.…”
Section: Smooth Muscle Cell Proliferation and Migrationmentioning
confidence: 99%
“…Apoptosis of vascular cells was a prominent feature of blood vessel remodeling that occurs during normal development and many disorders of the vessel wall. It had been demonstrated that the overall number of apoptotic cells and activity were reduced in varicose compared with non-varicose veins (Bujan et al 2000;Ascher et al 2001). Ducasse et al provided evidence of decreased programmed cell death in the medial layer of human primary varicose veins (Ducasse et al 2008).…”
Section: Go Name Degree Apoptosis 10mentioning
confidence: 99%